FACTORS AFFACTING SOCIAL NETWORK INTERPERSONAL TRUST SCALE FOR HIGH SCHOOL STUDENTS IN NAKHONSAWAN : A MULTIGROUP ANALYSIS - ปานทอง, อาวีพร; มงคลปัญญา, อภิเดช (Progress in Applied Science and Technology, 2019)
The objectives of this research were to study the factors affecting social network interpersonal trust scale for high school students in Nakhonsawan province in three points consist of (1) behavior (2) direct and indirect influence and accuracy theoretical of model (3) invariance of model between male and female. This study uses data from a questionnaire. The participants of this study were 2,280 high school students who enrolled in academic year 2017 by randomly selected based on multi-stage random procedures. The results were as follows: (1) behavior of social network interpersonal trust scale was high level (2) direct and indirect influence as well as accuracy theoretical of model were consistent with the empirical data (3) the model between male and female was invariance under considered specifications.